Ethics and sustainability in global supply chain management - Akkucuk, Ulas 1975- (Advances in logistics, operations, and management science (ALOMS) book series, 2017)
"[This book] is a comprehensive reference source for the latest scholarly material on organizational procedures and methods that ensure environmental sustainability, while maintaining effective production processes. Highlighting the most innovative topics and perspectives, such as life cycle costing, waste management, and business leadership, this book is ideally designed for professionals, academics, practitioners, graduate students, and researchers interested in developing green supply chain processes" - Provided by publisher